The Influence of Human, Organization, and Technological Factors on User Satisfaction of the MCH E-Cohort Application in Jambi (Case Study of Jambi City Puskesmas) - Dustar, Ghinanissa Azzahra; Sri Achadi Nugraheni; Purnami, Cahya Tri (Jurnal Multidisiplin Madani, 2024)
The study aims to determine the direct influence of Human, Organizational, and Technological Factors on Maternal and Child Health (MCH) e-Cohort user satisfaction. This type of research is quantitative research using SEM-PLS. using primary data with a total sampling of 78 respondents from twenty health centers in Jambi City. The results showed that there was a direct relationship between Human and Technological factors on MCH e-cohort user satisfaction at the Jambi City Health Center, and there was no relationship between Organization and MCH e-cohort user satisfaction at the Jambi City Health Center